The Analysis of Factors Affecting Student Decisions in Selecting Sharia Economics Study Program at The Faculty of Islamic Religion Muhammadiyah University Yogyakarta - RUSANDRY, Rusandry; SAMSUDDIN, Ardian (Integration: Journal Of Social Sciences And Culture, 2023)
Purpose:This study analyzes factors influencing students to take the Yogyakarta Muhammadiyah University's Islamic Economics program. The factors that researchers will study include interest, motivation, parental status, and employment which are expected.Methodology: This study uses a questionnaire method by making a list of questions and giving them to respondents in the hope of responding to these questions.Findings:Measurement variable is done by Likert scale using the suspension method. The population in this study were undergraduate students at the Faculty of Religion Islam Department of Sharia Economics at Yogyakarta Muhammadiyah University.Implication:The sampling method was carried out by accidental sampling, a sampling technique based on coincidence/incidental encounter researchers. It can be used as a sample if viewed by someone who coincidentally encountered it; it is suitable as a data source.